A sight of zinc corrosion in various alkaline media - W.M.I.W. Ismail; N.S.W. Zulkefeli; M.N. Masri (Universiti Malaysia Kelantan, 2016)
This review concentrates on corrosion properties that expose to zinc by various alkaline media. The assumption has been advanced that zinc corrodes electrochemically in the first stage of exposition, but the chemical corrosion prevails after a longer time. Different types of electrolyte had been tested on zinc such as sodium chloride, sodium hydroxide and potassium hydroxide. Each of alkaline media can produced corrosion product such as zinc hydroxide chloride, zinc hydroxide carbonate, zinc oxide, and zinc hydroxide. The production of corrosion products is depending on the carbon dioxide content that introduced to the air. Potassium hydroxide is the highest and active alkaline where it contains the highest ionic conductivity potassium ions, K+ after hydronium, H3O+ among the cations and hydroxide, OH ̄ has the highest ionic conductivity among the anions.